Organizational Communication : approaches and processes - Millar, Katherine (From the Wadsworth In Communication Studies, 2006)
Thomson Wadsworth is committed to providing you with the most contemporary learning solutions in the field of communication studies. That commitment applies to the concepts you learn in the classroom and the real skills you carry away with you. At Thomson Wadsworth, we knou that the students of today will be the professionals of tomorrow, and we welcome the opportunity to partner with you on your journey to lifelong learnnig... every step of the way.